Mandibuloacral dysplasia and LMNA A529V mutation in Turkish patients with severe skeletal changes and absent breast development - Ozer, Leyla; Unsal, Evrim; Aktuna, Suleyman; Baltaci, Volkan; Celikkol, Pelin; Akyigit, Fatma; Balci, Sevim (Lippincott Williams & Wilkins, 2016)
Mandibuloacral dysplasia (MAD) is an autosomal recessive disorder characterized by acroosteolysis (resorption of terminal phalanges), skin changes (hyperpigmentation), clavicular hypoplasia, craniofascial anomalies, a hook nose and prominent eyes, delayed closures of the cranial sutures, lipodystrophy, alopecia, and skeletal anomalies. MAD patients are classified according to lipodystrophy patterns: type A and type B. The vast majority of MAD cases are caused by LMNA gene mutations. MAD patients with type A lipodystrophy (MADA) have been reported to have LMNA R527H, A529V, or A529T mutations. In this report, we describe two MADA patients with progressive skeletal changes, absent breast development, and cataract in addition to the classical MAD phenotype. Both patients were found to be homozygous for the Ala529Val mutation of the LMNA gene. Our female patient is the oldest MADA patient (59 years old) who has ever been reported with the LMNA mutation and also the LMNA Ala529Val mutation. This study is the second report on MADA patients with a homozygous Ala529Val mutation.
Keywords: A529V mutation; absence of breast development; acroosteolysis; lipodystrophy; LMNA gene; mandibuloacral dysplasia